Extreme politics : nationalism, violence, and the end of Eastern Europe - King, Charles, 1967- (Oxford University Press, 2010)
Why do some violent conflicts endure across the centuries, while others become dimly remembered ancient struggles among forgotten peoples? Is nationalism really the powerful force that it appeared to be in the 1990s? In this wide-ranging and readable set of essays, Charles King examines the conceptual intersection of nationalist ideology, social violence, and the political transformation of Europe and Eurasia over the last two decades. The end of communism seemed to usher in a period of radical change-an era of "extreme politics" that pitted nations, ethnic groups, and violent entrep